Onde Está Banksy? - Jose Roberto Schneedorf Ferreira da Silva (2009)
Banksy is a graffiti and stencils authorial code name, a tag looming to the walls, to the façades, to the streets, to the squares of England since the early 90's, spreading for so many other urban spaces around the world (from Europe to Latin America, from USA to Palestine), a transit, an attitude already typical of the new British street artists joint tribe. From suffixing, Banksy is a signature in possible nicknaming to the term bank, on the profit, consumption diminutives; on the barricade, obstacle, resistance superlatives. By his efficient and effective anonymity it's conjectured to hide a 34-year-old English man, Robert Banks, from Bristol. Another possibility would be the pseudonym sheltering a group of artists making an effort at the exact same plastic and conceptual reasoning (cheerful and philosophical, reflexive of the Real and theNow). Besides the street's public spaces, Banksy also operates in original interference and appropriation of other public spaces: amusement parks (like Disneyland), zoos, museums specially; in "art-intruders" which inserts his works ironically defrauding not only the surveillance, but even more the access, the selective process and the authorization. To probe to find him is to create concerning to the ideology and the humor of his anonymity an investigation, a search not for the person or the character, but for what depicts; for his art itinerary, for what it cause and impels, building a small landscape of our days andtacking a dialogue, maybe a dialectics, in an imaginary interview starting from the own sly artist words activity target, invisible target.